Pandangan Jürgen Habermas Tentang Iman dan Akal Budi dan Implikasinya bagi Diskursus Seputar Peran Publik Agama di Indonesia - Madung, SVD, Otto Gusti (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2024)
This essay describes the most important aspects of the relationship between religion and the state, especially in the case of Indonesia. It argues that, on the one hand, religion and belonging to one’s religion should be acknowledged as a fundamental human right, and on the other, religion should also be protected by the state. Unfortunately, most of the time the state seems to prioritise religion over the people. As a result, minority groups may experience marginalisation, violence, and discrimination. In this regard, I will show that Habermas' view of the relation between reason and faith offers a cogent framework for structuring Indonesia's normative interaction between politics and religion. This paper makes the case that the state's function in the Indonesian pluralistic society is to ensure religious freedom rather than to defend religion. Habermas holds that religion in has a substantial role in the public sphere even in a secular society. On the other hand, religions in a pluralistic society must also learn to reconcile disparities of their core ethical and metaphysical ideas. As a result, religions living in Indonesia may contribute to uphold democracy, human rights, equality, and freedom.AbstrakTulisan ini menjelaskan aspek-aspek terpenting dalam hubungan antara agama dan negara, khususnya di Indonesia. Saya berpendapat bahwa, di satu sisi, memeluk sebuah agama harus diakui sebagai hak asasi manusia, dan di sisi lain, agama juga harus dilindungi oleh negara. Sayangnya, seringkali negara tampaknya lebih memprioritaskan agama daripada manusia. Akibatnya, kelompok minoritas dapat mengalami marjinalisasi, kekerasan, dan diskriminasi. Dalam hal ini, saya akan menunjukkan bahwa pandangan Habermas tentang hubungan antara akal budi dan iman menawarkan kerangka kerja yang masuk akal untuk menata interaksi normatif antara politik dan agama di Indonesia. Fungsi negara dalam masyarakat Indonesia yang majemuk adalah untuk menjamin kebebasan beragama, bukan untuk membela agama. Habermas juga berpendapat bahwa agama memiliki peran penting dalam ruang publik bahkan dalam masyarakat sekuler. Di sisi lain, agama-agama dalam masyarakat majemuk juga harus belajar untuk mendamaikan perbedaan-perbedaan dalam gagasan-gagasan inti etika dan metafisika mereka. Dengan demikian, agama-agama yang hidup di Indonesia dapat berkontribusi dalam menegakkan demokrasi, hak asasi manusia, kesetaraan, dan kebebasan.